Comparison of different models for the analysis of rayleigh fading channels - Mahboob, Mahdin; Alam, F.M. Sajidul; Muna, Sittul (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.